#212 Simultaneous estimation of antihypertensive agents by two different UV methods - Sawaikar, Leena; Usgaonkar, Ketaki (Journal of Pharmaceutical Chemistry, 2022)
The aim of this study is to develop and validate two analytical methods for the simultaneous estimation of Amlodipine besylate (AMLO) and Hydrochlorothiazide (HCTZ) using simultaneous equations method and absorption ratio method by UV spectrophotometry. Method A involved the simultaneous equations method. The two wavelengths, 238 nm (λmax of AMLO) and 271 nm (λmax of HCTZ), were chosen for the formation of simultaneous equations method. Beer Lambert’s law was obeyed in the concentration range of 5-35 μg/mL for amlodipine besylate and hydrochlorothiazide, respectively with a correlation coefficient (r2) greater than 0.990. For Q absorbance ratio method, 253 nm (isosbestic point) and 271 nm (λmax of HCTZ) were chosen as the two wavelengths for analysis. A concentration range of 5-35 μg/mL for AMLO and HCTZ, respectively, with a correlation coefficient (r2) greater than 0.990, was selected as per beer’s law. The developed method validation was done as per ICH guidelines. The % assay of AMLO and HCTZ were found to be 99.670 % and 101.086% by simultaneous equations method and 98.038% for amlodipine and 100.230% by absorption ratio method, which were within the acceptable limit. The developed methods were simple, sensitive, accurate, precise, and robust and can be used for the simultaneous estimation of the two drugs in tablet formulation.